Purdue Improved Crop Storage (PICS) bags for safe storage of groundnuts. (October 2015) - Sudini, H.; Ranga Rao, G.V.; Gowda, C.L.L.; Chandrika, R.; Margam, V.; Rathore, A.; Murdock, L.L.
Abstract: Groundnut seeds are prone to quality deterioration and damage due to improper storage. Hermetic storage of pods offers a novel, sustainable and ecologically safe alternative over traditional methods. In this paper, we demonstrate the efficacy of triple-layer "Purdue Improved Crop Storage (PICS)" bags, (that comprises of two inner high density polyethylene bags and one outer woven polypropylene bag), for protecting pods from quality deterioration, damage by bruchids ( Caryedon serratus ) and aflatoxin contamination ( Aspergillus flavus ). Custom made triple-layer bags were used and pods (of cv ICGV 91114) were placed @ 2 kg/bag. Over four months of storage under ambient conditions, triple-layer bags supported retention of seed weight, germinability and oil content significantly better than cloth bags. Further, under both natural and artificial infestations with A. flavus, seed aflatoxins levels were lower in PICS bags compared to cloth bags. Toxin accumulation in PICS bags deliberately infested with bruchids and A. flavus was less compared to cloth bags under similar conditions. Bruchid damage to pods was less in PICS bags versus cloth bags in all cases. Our results suggest the superiority of triple-layer PICS bags over cloth bags in protecting seed viability, seed weight and oil content while safeguarding the groundnuts from bruchids and retarding toxin accumulation. Highlights: The efficacy of hermetic storage of groundnuts using PICS bags was evaluated. Groundnut storage in PICS has less bruchid damage and aflatoxin contamination. PICS bags safely retained groundnut seed weight, germinability and oil content. Groundnut storage using PICS is a viable and ecologically safe storage method.